The Development of Memory Game Media for Improving Letter and Number Recognition Skills in Early Childhood - Nurkhalisa, Nurkhalisa; Rusmayadi, Rusmayadi; Herman, Herman; Herlina, Herlina; Hajerah, Hajerah; Hakim, Abdul (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Recognizing letters and numbers is essential in early childhood as a foundation for literacy and numeracy. This study aimed to improve these skills through memory game media. Using a Research and Development (R&D) approach with the Thiagarajan 4D model (define, design, develop, disseminate), the research involved 3 teachers and 15 students. Data were collected through observation, interviews, and questionnaires, analyzed both quantitatively and qualitatively. Results showed an increase in recognition skills from 61% (pre-test) to 71% (post-test). Teacher responses rated the media at 94.06% effectiveness. The Wilcoxon signed-rank test confirmed significant improvement (66 positive ranks; p < 0.05). Memory game media proved effective for enhancing letter and number recognition in early childhood. The study offers practical insights for integrating interactive media into early education and encourages further research for broader application.┬á┬á